Digital Democracy: The Evolution of Indonesia Electoral Politics - Imawan, Riswanda (UIN Sunan Ampel Surabaya, 2023)
The digital age is ushering in transformative changes in the electoral political landscape around the world. Including Indonesia, as a dynamic democracy, is also a country that cannot avoid this change. The collaboration between advances in digital technology and politics has reshaped how election campaigns are run, information is disseminated, and Indonesian citizens engage with the democratic process. This article examines the challenges and opportunities arising from the integration of digital technology in the democratic order in this case elections in Indonesia. The purpose of this study is to analyze the impact of the evolution of digital democracy on the electoral process in Indonesia, from voter outreach and campaign strategies to how to maintain democratic integrity. This research draws on a comprehensive review of the existing literature, combined with an analysis of democratic processes in Indonesia. Qualitative and quantitative data are used to illustrate the changing nature of electoral politics in Indonesia's digital era. This article shows that digital democracy in terms of electoral evolution will be inevitable and will continue to develop along with the times, Indonesia is an affected country. This is evidenced by how digital technology has democratized political participation in Indonesia, encouraging increased citizen engagement and challenges and opportunities.